A proposed approach for standardized reporting of data linkage processes and results. - Yinshan Zhao; Mike Jarrett; Kimberlyn McGail; Brent Hills (International Journal of Population Data Science, 2022)
Objectives Population Data BC (PopData) is an agency in British Columbia, Canada, that routinely performs linkages of various administrative and researcher-collected data to a population spine. We developed a linkage report template in order to increase transparency of linkage process and outcome for end users and data providers.